From Conversation To Competence: The Influence Of ChatGPT Use And Learning Motivation In Improving Self-Directed Learning - Indriani, Wini; Nauval Nawwaf, Muhammad; Yundianto, Devie; Erikha, Fajar; Khatami, Muhammad (Academic Journal of Psychology and Counseling, 2024)
The rising popularity of ChatGPT has an impact on student learning behavior. This study focused on how ChatGPT use and learning motivation affect students' self-directed learning. This study involved 98 respondents, who were undergraduate and master's students and had used ChatGPT for learning at least 1 (one) time, selected using the convenience sampling technique. This research employed multiple regression analysis methods. The research results show a significant and positive influence of ChatGPT use (R=0.747, β=0.419, p<0.01) and learning motivation (R=0.802, β=0.553, p<0.01) on self-directed learning. The study also found that learning motivation provided higher contribution to self-directed learning than ChatGPT use. These findings offer new insights to the existing knowledge on the role of artificial intelligence and learning motivation in supporting self-directed learning in students.